Enhancement heat transfer characteristics in the channel with Trapezoidal rib–groove using nanofluids. (March 2015) - Al-Shamani, Ali Najah; Sopian, K.; Mohammed, H.A.; Mat, Sohif; Ruslan, Mohd Hafidz; Abed, Azher M.
Abstract: Numerical study of heat transfer due to turbulent flow of nanofluids through rib–groove channel have been investigated. The continuity, momentum and energy equations are solved by the finite volume method (FVM). Four different rib–groove shapes have been examined. Four different types of nanoparticles, Al2 O3, CuO, SiO2, and ZnO with different volumes fractions in the range of 1–4% and different nanoparticle diameter in the range of 25–70 nm, have been also studied. The computations are performed under constant temperature over a range of Reynolds number (Re) 10, 000–40, 000. Results indicate that the Trapezoidal with increasing height in the flow direction rib–trapezoidal groove has the best heat transfer rate and high Nusselt number. It is also found that the SiO2 – nanofluid has the highest value of Nusselt number in comparison with the other type of nanofluids. The Nusselt number increases as the volume fraction increases and it decreases as the nanoparticle diameter increases. The present study shows that these Trapezoidal rib–groove using nanofluids have the potential to dramatically increase heat transfer characteristics and thus can be good candidates for the development of efficient heat exchanger device.